Efektivitas Rendaman Daun Jati (Tectona grandis Linn.f) Dalam Mewarnai Stadium Telur Parasit STH (Soil Transmitted Helminth) - Hastuti, Puji; Haryatmi, Dwi (Jurnal Farmasi (Journal of Pharmacy), 2021)
Worm disease is a health problem that is widely found in the world, nearly 2 billion people are infected with the Soil Transmitted Helminth (STH). Worms belonging to STH are Ascaris lumbricoides, Trichuris trichiura and hookworms (Ancylostoma duodenale and Necator americanus). The diagnosis of intestinal worms is confirmed by microscopic examination of the feces supported by staining. Eosin and lugol have been used as dyes on microscopic examination of feces. Teak leaf (Tectona grandis Linn.f) contain anthocyanin compounds that can be used as natural dyes. The purpose of this study was to determine the ability of soaked teak leaf to color the egg stage of the STH parasite when compared with eosin 2% and lugol 2%. The stool examination method used was sedimentation method. The teak leaf soak was obtained by soaking teak leaf with ethanol 96% and concentrated HCL for 24 hours. The results of staining using teak leaf gave an effective value of 100% on Ascaris sp. ang Trichuris sp. eggs, and gave an effective value of 66,7% on Hookworm eggs. Based on the Chi-square test calculations and the Fisher Exact tables, it can be determined that the teak leaf has such significant capabilities as eosin 2% and lugol 2% in coloring the eggs stage of the STH parasites.